دور الادارة المدرسية في تخفيف من ظاهرة العنف المدرسي من وجهة نظر التلاميذ - عوين، مختار, حمدان، ياسين (جامعة الوادي university of Eloued, 2020)
الملخص: جاءت الدراسة لتكشف عن دور الإدارة المدرسية في التخفيف من ظاهرة العنف المدرسي، ولقد قمنا بهذه الدراسة نظرا للواقع المعاش في المؤسسات التربوية الجزائرية، فالعنف المدرسي أصبح يعيق المردود التعليمي من خلال هذه الدراسة يتم الكشف عن دور الادارة المدرسية في محاولة لتخفيف من ظاهرة العنف المدرسي ومن هذا المنطق جاء التساؤل الرئيسي كالآتي: كيف تساهم الادارة المدرسية في التخفيف من ظاهرة العنف المدرسي؟ وضعت الدراسة ثلاث فرضيات فرعية وهي كالآتي: - يساهم الطاقم الاداري للمؤسسة في التخفيف من السلوكيات العنيفية لدى التلاميذ - تساهم العلاقات التربوية الجيدة للأستاذ في معالجة السلوكيات العدوانية لدى التلاميذ - يساهم التكامل بين أعضاء الادارة المدرسية وأولياء التلاميذ في معالجة السلوكيات العنيفة وقد استخدم المنهج الوصفي التحليلي وهذا لوصف الظاهرة المدروسة وتحليلها كما وكيفا وتفسير البيانات و ابراز دور الادارة المدرسية كما اعتمدنا على مجموعة من ادوات جمع البيانات والتي تمثلت في الملاحظة المباشرة والاستبيان للوصول الى انجع أسلوب في التعامل وكانت الدراسة موجهة إلى تلاميذ التعليم الثانوي لأنه يتمتعون بمرحلة عمرية مميزة من حيث النمو العقلي والمعرفي والعاطفي والى ردود فعل التلاميذ ومعالجة مشاكلهم حيث اجريت هذه الدراسة بأربع ثانویات استخدمت العينة العشوائية البسيطة والتي شملت منتان تلميذ وتلميذة. وكخلاصة فإن العنف سلوك سلبي على التلميذ والمؤسسة وهذا ما يستدعي الى وجود أدارة مدرسية فعالة وقائمة للتقليل مكن هذه الظاهرة ولا يختصر هذا الدور على الادارة المدرسية فحسب بل على كل من يهمه هذا التلميذ ويهمه مستقبله العلمي والعملي. Résumé :فرنسية أو انجلزية The study came to reveal the role of the school administration in alleviating the phenomenon of school violence, and we have done this study in view of the lived reality in Algerian educational institutions. School violence has become an impediment to educational outcomes. Through this study, the role of the school administration in an attempt to reduce the phenomenon of school violence and This logic came to the main question as follows: How does the school administration contribute to alleviating the phenomenon of school violence? The study established three sub hypotheses, which are as follows: - The institution’s administrative staff contributes to reducing violent behavior among students The good educational relations of the professor contribute to addressing the aggressive behaviors of the students - Integration between members of the school administration and parents of pupils contributes to addressing violent behaviors The descriptive and analytical approach was used to describe the studied phenomenon, analyze it in terms of quantity and quality, interpret data and highlight the role of school administration. We also relied on a set of data collection tools, which were represented in direct observation and questionnaire to reach the most effective method of dealing. The study was directed to secondary education pupils because they have a distinct age stage. In terms of mental, cognitive and emotional development, the students' reactions and the treatment of their problems, as this study was conducted in four secondary schools, a simple random sample was used that included two hundred male and female students. In conclusion, violence is a negative behavior on the student and the institution and this calls for the existence of an effective and existing school administration to reduce this phenomenon. This role is not limited to school administration only, but to everyone who cares about this student and is concerned with his scientific and practical future.
دراسة ميدانية على عينة من تلاميذ ثانويات الرباح والزقم - ولاية الوادي
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع التربية
Keywords: الإدارة المدرسية، العنف المدرسي; Administration scolaire, violence scolaire; School administration, school violence